Autoimmune Polyendocrinopathy Induced by an Antibody (KN046) That Simultaneously Inhibits PD-L1 and CTLA-4: A Case Report and Literature Review - Li M; Wu C; Liu Y; Zhang R; Yang Q; Shi Z; Sun W; Hu X (Diabetes, Metabolic Syndrome and Obesity, 2022)
Min Li,* Chenchen Wu,* Yan Liu, Ranran Zhang, Qingqing Yang, Zhaoming Shi, Weihua Sun, Xiaolei Hu Department of Endocrinology, The First Affiliated Hospital of Bengbu Medical College, Bengbu, Anhui Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaolei Hu, Department of endocrinology, The First Affiliated Hospital of Bengbu Medical College, No. 287 Changhuai Road, Bengbu, Anhui Province, 233000, People’s Republic of China, Tel +8613855216339, Email caesar80@163.comAbstract: Endocrine adverse reactions are one of the most common adverse reactions in the treatment of immune checkpoint inhibitors (ICIs), mainly involving the pituitary gland, pancreas, thyroid gland, adrenal gland and other glands, resulting in corresponding endocrine dysfunction. We report a 45-year-old man with non-small-cell lung cancer who developed hypophysitis 11 months after initiation of treatment with an anti-PD-L1/CTLA-4 bispecific antibody (KN046) that blocks both programmed death ligand-1 (PD-L1) and cytotoxic T-lymphocyte antigen-4 (CTLA-4), followed by regular oral replacement doses of prednisone and levothyroxine tablets. The patient was diagnosed with type 1 diabetes mellitus (T1DM) with diabetic ketoacidosis (DKA) 25 months after the start of immunotherapy, presenting with acute hyperglycemic symptoms, ketoacidosis, and negative diabetic autoantibodies. By describing a case of KN046 immunotherapy involving multiple endocrine glands and reviewing relevant literature, we were able to summarize the clinical characteristics of KN046 immunotherapy-induced endocrine system-related immune-related adverse events (irAEs) for use in early detection, diagnosis and treatment.Keywords: type 1 diabetes, immune checkpoint inhibitors, immune-related adverse reactions, KN046